PENGARUH METODE EKSPERIMEN TERHADAP HASIL BELAJAR MATA PELAJARAN IPA MATERI PERUBAHAN ENERGI BUNYI MELALUI PENGGUNAAN ALAT MUSIK DI KELAS IV SEKOLAH DASAR - Septiani, Hani (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Commonly, science teaching and learning were still focused on the teacher. The teacher gave less direct experience to the students like experiment and observation activities. Commonly, science learning still used presentation method and giving exercises with questions. Students do not have the chance to have experiments or observation. The innovation in teaching-learning can apply one of the teaching method, namely by experiment method, the problem formulation of this research was whether or not there was an effect of the experiment method toward the students’learning outcome for the fourth graders of elementary school. The learning result observed consisted of three aspects: cognitive, affective, and psychomotor aspects. This research is quantitative research with experiment design. The subject of the research was the fourth graders of elementary school consisting of two classes, the students of class IVA with 19 students as the control class, and the students of class IVB with 20 students as the experiment class. The technique of collecting the data was by posttest for the cognitive aspect, hard work questionnaire for the affective aspect, and work performance for the psychomotor aspect. The material used in this research was all in the topic of energy changes through the use of instrumental music. The data gained was then analyzed by Mann Whitney test. Based of the calculation, it could be concluded that three was an effect of experiment method toward the students’ science learning outcome on cognitive and psychomotor aspects, however, it had no effect on the students’ science learning outcome on the affective aspect of the fourth graders of elementary school.